Pengaruh Kualitas Produk dan Brand Trust Terhadap Minat Beli Produk Personal Care Pria Kahf di Kota Bima - M. Irgi Am Fahraiji; Ismunandar; Sri Ernawati (Tamilis Synex: Multidimensional Collaboration, 2026)
This study aims to analyze the effect of product quality and brand trust on consumers' purchase intention toward Kahf men's personal care products in Bima City. The research employed a quantitative approach with an associative design to examine the relationships among the variables. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling, consisting of consumers aged 18 years and above who had previously purchased and used Kahf products. The collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation and determination coefficient analysis, as well as t-tests and F-tests. The findings indicate that product quality has a positive and significant effect on purchase intention (β = 0.218, p < 0.001), while brand trust also has a positive and significant effect on purchase intention (β = 0.669, p < 0.001). Simultaneously, product quality and brand trust significantly influence purchase intention, with an F-value of 99.509 (p < 0.001). The coefficient of determination (R² = 0.672) indicates that 67.2% of the variation in purchase intention is explained by the two independent variables. These findings suggest that improving product quality and strengthening consumer trust in the Kahf brand are essential strategies for increasing consumers' purchase intention in the men's personal care market.